From old to new developmentalism in Latin America - Bresser-Pereira, Luiz Carlos (2009)
The failure of the Washington Consensus and of macroeconomic policies based on high interest rates and non-competitive exchange rates to generate economic growth prompted Latin America to formulate national development strategies. New developmentalism is an alternative strategy not only to conventional orthodoxy but also to old-style Latin American national developmentalism. While old national developmentalism was based on the tendency of the terms of trade to deteriorate and, adopting a microeconomic approach, proposed economic planning and industrialization, the new nationaldevelopmentalism assumes that industrialization has been achieved, although in different degrees by each country, and argues that, in order to assure fast growth rates and catching up, the tendency that must be neutralized is that of the exchange rate to overvaluation. Contrary to the claims of conventional economics, a capable state remains the key instrument to ensure economic development, and industrial policy continues to be necessary; but what distinguishes the new approach is principally growth with domestic savings instead of with foreign savings, a macroeconomic policy based on moderate interest rates and a competitive exchange rate instead of the high interest rates and the overvalued currencies prescribed by conventional orthodoxy.